The role of ecological constraints on expertise development - Araujo, D.; Fonseca, C.; Davids, K.; Garganta, J.; Volossovitch, A.; Brandao, R.; Krebs, R. (Talent Development & Excellence, 2010)
The role of ecological constraints on the acquisition of sport expertise is gaining attention in sport science, although more research is needed. In this position paper we provide an ecological explanation for expertise acquisition, as alluding to qualitative data that support the idea that unconventional, even aversive, environmental constraints may play an important role in the development of world-class athletes. We exemplify this argument by profiling the role of unconventional practice environments using association football in Brazilian society as a task vehicle. Contrary to the traditional idea that only deliberate training and development programmes can lead to the evolution of expertise, we propose how expert performance might be gained through highly unstructured activities in Brazilian football, that represent a powerful and little understood implicit environmental constraint that can lead to expertise development in sport.